Temperature Monitoring System for 3 Phase Electric Arc Furnace (EAF) Transformer Cooling - Afandy, Moh; Mubarak, Abdul Haris; Rianto, Muhammad Ikbal (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
The Electric Arc Furnace (EAF) transformer is a key component in the steel melting system using a furnace. The transformer functions to convert the electrical voltage from the main electrical network into the electrical voltage needed to form an electric arc in the melting furnace. In this research, the EAF transformer configuration uses a delta-wye configuration with a furnace melting capacity of 10 kg nickel ore. In its working system, this transformer will produce a very high current when the melting system is running. So this process will produce excessive heat on the EAF transformer side. As a result of the significant heat generated in the melting process, this transformer is equipped with a cooling system in the form of transformer oil which is a heat release medium and maintains the correct operating temperature. An appropriate temperature monitoring system will increase the work efficiency of the transformer and prevent excessive damage to the system. The sensor used in the design is the RTD PT 100 sensor which is installed at 7 measurement points. The main controller for data collecting and data processing used is a Siemens PLC. Data that has been processed on the main control device is transmitted to the IoT cloud server using a V-box device. As a human machine interface (HMI) web SCADA is used to read data in real time. From the results of the tests that have been carried out, the highest error presentation value obtained in measurements on the T phase is 0.05%. Meanwhile, when measuring the transformer oil sensor, an error value of 0% was obtained.